Clarifying the switching layer transformation through analysis of an abnormal I–V curves with increasing set compliance current in oxide-based resistive random access memory. (2nd September 2021) - Lin, Shih-Kai; Chang, Ting-Chang; Lien, Chen-Hsin; Wu, Cheng-Hsien; Xu, You-Lin; Yang, Chih-Cheng; Huang, Wei-Chen; Wu, Pei-Yu; Zhang, Yong-Ci; Chou, Sheng-Yao; Huang, Hui-Chun; Wang, Kao-Yuan; et al.
Abstract: This work investigates an abnormal rising current in high resistance state (HRS) during the reset process that occurs when increasing the sweeping set compliance current (SCC). When the SCC is increased, the HRS current read at a lower voltage (−0.1 V) remains similar, yet exhibits a gradual rise when read at a higher voltage (−0.8 V). In order to clarify this abnormal phenomenon, the current fittings were performed to obtain the corresponding switching layer (SL) properties after set operations with different SCCs. Furthermore, COMSOL electric field simulations with different SL properties were executed to verify the mechanism.